Tingkat Upper Body Strength Siswa Ekstrakurikuler Bolavoli - Bahri, Asep Saepul; Sutisna, Nana; Rezha, Mohamad (Universitas Galuh, 2022)
This study aims to determine the level of upper body strength of volleyball extracurricular students. The research method used is causal comparative. The population of this study at SMP Negeri 1 Malangbong, Garut Regency, amounting to 34 people. The research instrument used to collect data was the medicine ball javelin quadrathlon test. Based on data analysis using SPSS series 24, the results are based on the results of the independent sample t-test, it is proven that the value obtained is smaller than the two research groups (group A volleyball extracurricular and group B volleyball extracurricular). This shows that there is a difference but the difference is not too big. So the authors conclude that the mean or mean between group A volleyball extracurricular and group B extracurricular volleyball there is no difference. The conclusion is that there is no difference between group A volleyball extracurricular and volleyball extracurricular group B in increasing upper body strength. Suggestion: It is hoped that there will be further research that discusses upper body strength but by using different test instruments so that scientific knowledge will increase and develop.Penelitian ini bertujuan untuk mengetahui tingkat upper body strength siswa ekstrakurikuler bolavoli. Metode penelitian yang digunakan adalah kausal komparatif. Populasi penelitian ini di SMP Negeri 1 Malangbong Kabupaten Garut yang berjumlah sebanyak 34 orang. Instrumen penelitian yang digunakan untuk mengumpulkan data adalah medicine ball javelin quadrathlon test. Berdasarkan analisis data menggunakan SPSS serie 24 hasilnya adalah berdasarkan hasil uji independent sample t-test terbukti bahwa nilai yang didapat lebih kecil dari dua kelompok penelitian (kelompok A ekstrakurikuler bolavoli dan kelompok B ekstrakurikuler bolavoli). Hal ini memperlihatkan bahwa adanya perbedaan namun perbedaannya tidak terlalu besar. Sehingga penulis menyimpulkan bahwa rata-rata atau mean di antara kelompok A ekstrakurikuler bolavoli dengan kelompok B ekstrakurikuler bolavoli tidak terdapat perbedaan. Kesimpulannya bahwa tidak terdapat perbedaan antara kelompok A ekstrakurikuler bolavoli dengan kelompok B ekstrakurikuler bolavoli terhadap peningkatan upper body strength. Saran: Diharapkan adanya penelitian lanjutan yang membahas tentang upper body strength namun dengan menggunakan instrument test yang berbeda sehingga wawasan keilmuan semakin banyak dan berkembang.